Critical Engagement on Digital Sovereignty in International Relations: Actor Transformation and Global Hierarchy - Adonis, Abid A. (Global: Jurnal Politik Internasional, 2019)
The idea of digital sovereignty in the last twenty years increasingly reifies into chiefly policy making debates as the reaction of China’s determined activism on internet governance, Snowden’s case, and increasingly big internet corporations’ unchecked endeavors. International actors’ growing concerns on security, economy, data protection, and socio-political issues invoke new discourses on digital sovereignty since it bears global political consequences by nature. This stimulates recent intellectual debate in academic literature on how digital sovereignty affects (or be affected by) international politics. This article critically examines the development of digital sovereignty literatures. This article classifies literature taxonomically on four major themes: the conceptual development of digital sovereignty; actors in digital sovereignty; digital sovereignty and global internet governance; and categorical issues on digital sovereignty. This article argues that the development of literature on digital sovereignty is still largely dominated by state-centered and security-politics narrative. This article calls for global digital hierarchy and necessitates actor transformation approach in order to spur future exploration on digital sovereignty. Instead of drawing close-ended conclusion of the ongoing debate of digital sovereignty, this article positions itself as an intermediary text to drive more questions and call for broader potential development of the topic’s research agenda.